Screening for probiotic of lactic acid bacteria isolated from the digestive tract of a native Aceh duck (Anas platyrhynchos) - Yayuk Kurnia Risa; Sri Harimurti; Wihandoyo; Widodo Widodo (Society for Indonesian Biodiversity, 2020)
Abstract. Risna YK, Harimurti S, Wihandoyo, Widodo. 2020. Screening for Probiotic of lactic acid bacteria isolated from the digestive tract of a native Aceh duck (Anas platyrhynchos). Biodiversitas 21: 3001-3007. The lactic acid bacteria (LAB) isolated from the digestive tract of a native Aceh duck has emerged as a potential probiotic supplement for duck feed. In this study, we isolated the LAB from the digestive tract of an Aceh duck (Anas platyrhynchos) and identified the species and bacterial characteristics. Additionally, we isolated the LAB used in this study from the crop, proventriculus, ventriculus, duodenum, jejunum, ileum, and cecum of the native Aceh duck. Identification included the examination of morphology and physiology, followed by molecular identification by using 16S rRNA and sequence similarity tests for the bile salt hydrolase (bsh) gene. Bacterial isolation from the digestive tract of this duck resulted in 19 isolates with gram-positive, negative catalase, and non-motile characteristics. Of the 19 isolates, 11 isolates exhibited the ability to grow at 15°C, 37°C, and 45°C, with optimum growth at 37°C. From 11 isolates, only 6 were identified by using 16S rRNA primers and 5 were identified by using BSH primers. The identified LAB included Lactobacillus plantarum, Lactobacillus fermentum, and Pediococcus acidilactici. Hence, we conclude that Lactobacillus sp and Pediococcus sp. are potential probiotics that can be isolated and administered for duck feed.